Gastrointestinal manifestations and outcomes of hospitalised patients with COVID-19 disease - Poudel, Shekhar; Poudel, Sujan Chandra; Mishra, Aakash; Bhattarai, Tulsi Ram (Journal of Kathmandu Medical College, 2022)
Background: COVID-19 infection usually presents with respiratory symptoms. Many hospitalised patients of COVID-19 present with gastrointestinal symptoms which can alter the clinical outcomes of patients. Objectives: To characterise the gastrointestinal manifestations of COVID-19 patients requiring hospitalisation and their correlation with disease severity and clinical outcomes. Methods: This was a single centre prospective, observational, cohort study done at Kathmandu Medical College, a tertiary health care centre after ethical clearance. All consecutive hospitalised patients with COVID-19 disease admitted during May and June 2021 were included in the study after ethical clearance. Diagnosis of COVID-19 infection was done by RT-PCR. Gastrointestinal symptoms of abdominal pain, aguesia, nausea/vomiting, and diarrhoea were recorded on hospital admission and outcomes accessed at discharge. Data were analysed using SPSS v.24. Results: A total of 196 consecutive adult patients with COVID-19 infection were included in study. Gastrointestinal symptoms were recorded in 48 (24.5%) patients. The most frequent symptom was nausea/vomiting (23, 11.7%) followed by aguesia (19, 9.7%), diarrhoea (14, 7.1%), and abdominal pain (8, 4.1%). There was no significant association between duration of hospital stay and presence of gastrointestinal symptoms (10.15 vs 10.95 days; p = 0.481). No significance was seen on association of gastrointestinal symptoms with ICU admission and mortality but requirement of mechanical ventilation was significantly higher in patients without symptoms (10.4 vs 23.6%; p = 0.048). Conclusion: Significant proportion of patients with COVID-19 infection can have gastrointestinal manifestations. Presences of these symptoms do not have any association with the final clinical outcome of the patient.